LGG-02. A PHASE II PROSPECTIVE TRIAL OF SELUMETINIB IN CHILDREN WITH RECURRENT/PROGRESSIVE PEDIATRIC LOW-GRADE GLIOMA (PLGG) WITH A FOCUS UPON OPTIC PATHWAY/HYPOTHALAMIC TUMORS AND VISUAL ACUITY OUTCOMES: A PEDIATRIC BRAIN TUMOR CONSORTIUM (PBTC) STUDY, PBTC-029B. (23rd April 2019) - Fangusaro, Jason; Onar-Thomas, Arzu; Poussaint, Tina Young; Wu, Shengjie; Ligon, Azra H; Lindeman, Neal; Banerjee, Anu; Packer, Roger J; Kilburn, Lindsay B; Goldman, Stewart; Pollack, Ian F; Jakacki, Regina I; et al.
Abstract: BACKGROUND: Pediatric low-grade glioma (pLGG) is the most common CNS tumor of childhood. Progression-free survival (PFS) is much lower than overall survival emphasizing the need for alternative treatments. In addition, many children suffer functional morbidities such as visual and motor disturbances. Recently, there has been an appropriate prioritization of functional outcomes in children with pLGG. METHODS: We present the results of a PBTC phase II trial evaluating selumetinib, (AZD6244, ARRY-142886) a MEK-1/2 inhibitor, in children with recurrent/progressive pLGG on 2 strata, including visual outcomes. RESULTS: Stratum 3 enrolled Neurofibromatosis type 1 (NF1)-associated pLGG. Ten of 25 (40%) eligible patients had partial response (PR), 14/25 (56%) had stable disease (SD) and 1/25 (4%) had progressive disease (PD); 2-year PFS was 96 + 4%. Ten patients with optic pathway glioma (OPG) were evaluable for visual acuity (VA) at baseline and 1 year. VA improved in 2/10 patients (20%) and was stable in 8/10 (80%). One patient (10%) had improvement in visual fields (VF) and 9 patients (90%) had stable VF. Stratum 4 included patients with non -NF1-associated recurrent/progressive hypothalamic and OPG. Five of 25 (20%) eligible patients had PR, 16/25 (64%) had SD and 4 (16%) had PD; 2-year PFS was 78 + 8.5%. Nineteen of 25 patients were evaluable for VA. VA improved in 4/19 patients (21%), was stable in 13/19 (68%) and worsened in 2/19 (11%). Five patients (26%) had improved VF and 14 (74%) had stable VF. The most common toxicities included grade 1/2 CPK elevation, diarrhea, hypoalbuminemia and rash. Rare grade 3 toxicities included elevated CPK, rash and paronychia. CONCLUSIONS: Selumetinib was tolerable and effective in treating children with NF1-associated and sporadic recurrent/progressive hypothalamic and OPG based upon radiographic response and PFS. Twenty-seven of 29 (93%) evaluable patients had stable or improved vision based on VA and VF testing.